A Comprehensive Profile of Chemokine Gene Expression in the Tissues of the Female Reproductive Tract in Mice. (2nd April 2020) - Menzies, Fiona M.; Oldham, Rachel S.; Waddell, Carolann; Nelson, Scott M.; Nibbs, Robert J. B.
ABSTRACT: Homeostatic leukocyte trafficking into and within the female reproductive tract (FRT) contributes to fertility and reproductive health. It is unclear how this process is regulated in the anatomically distinct reproductive tissues, or whether the genes involved are affected by cyclical changes in reproductive hormones. In tissues such as skin and intestine, mouse studies have defined evolutionarily conserved molecular mechanisms for tissue-specific homing, interstitial positioning, and leukocyte egress. Chemokine family members are invariably involved, with the chemokine expression profile of a tissue regulating leukocyte content. Reproductive tissues (ovary, vagina, cervix, uterine horn) of 8 week old virgin female C57BL/6 mice ( n = 20 ) were collected, and expression of mRNA for leukocyte markers and chemokines conducted by qPCR. Lymphocytic and myeloid cell populations within the uterus, cervix, bone marrow and PALN from virgin C57BL/6 mice were determined by flow cytometric analysis. Variation in leukocyte content between reproductive tissues is evident, with the uterus and cervix containing complex mixtures of lymphocytes and myeloid cells. Twenty-six chemokine genes are expressed in the FRT, many by several component tissues, some preferentially by one. Most striking are Xcl1 and Ccl28, which are restricted to the uterus. Ccl20 and genes encoding CXCR2 ligands are primarily transcribed in cervix and vagina. Ovary shows the lowest expression of most chemokine genes, with the notable exception of Ccl21 and Ccl27 . We also identify eight chemokines in the vagina whose expression fluctuates substantially across the oestrous cycle. These data reveal complex chemokine networks within the FRT, and provide a framework for future studies of homeostatic leukocyte trafficking into and within these tissues. Abbreviations : BM: bone marrow; DC: dendritic cell; DN: double negative; FRT: female reproductive tract; FSC: forward scatter; NK: natural killer; PALN: para-aortic lymph node; SSC: side scatter; Tregs: regulatory T cells